Evaluation of systemic acquired resistance inducer and Phatogenesis Related-gene expression profiling in dieback infected-papaya - Samsuddin, Normahfuzah Husna (2021)
Erwinia mallotivora was identified as a pathogen of papaya dieback disease and has become one of the most destructive to the papaya industry. Pathogenesis-related (PR) genes are considered plant defense genes, where they can prevent or reduce the pathogen and insect attacks. Accumulation of PR genes is closely related to developing systemic acquired resistance (SAR) in plants. PR expression can be induced by signaling compounds such as ethylene, salicylic acid (SA), jasmonic acid (JA), mechanical wounding and microbial infection. In this study, salicylic acid (SA) was used as a chemical inducer and their effectiveness in inducing SAR in papaya for enhanced disease resistance to papaya dieback was evaluated. Carica papaya was grown in a glasshouse with Randomized Complete Block Design (RCBD) arrangement. SA treatment with three concentrations (1 mM, 3 mM, 5 mM) and observation of papaya seedling physiology was done to study the effect of SA on plant growth. E. mallotivora inoculations were applied to the papaya seedlings after 1 month of SA applications, and disease assessment was evaluated weekly. The application of SA as a chemical inducer to papaya seedlings showed no negatively effect on Eksotika I seedlings growth. For disease assessment, significant differences were recorded between the control and the treatments. Among 10 PR genes analyzed, only Osmotin, CPBI_13 and CPBI_17were down-regulated for all SA-treatments. The rest (PR1 genes, CPBI_3, CPBI_4 and peroxidase) can be a potential SAR marker in the future. The induced expression of PR genes correlates with the activation of defence responses where they serve as excellent molecular markers of the papaya plant’s defence. From this study, it was shown that salicylic acid is effective in inducing SAR in papaya. The results of this study can improve our understanding of the SAR mechanism and reveal PR genes marker for further research.